Guest editorial: marketing via smart technologies in hospitality and tourism - Stylos, Nikolaos; Jiang, Yangyang; Pergelova, Albena (My University, 2024)
Smart technologies are revolutionizing services across various sectors. Smartness creates an innovative substratum of technological advances that offer new ways for service optimization via capitalizing on intelligence capabilities to best serve consumer needs (Stylos et al., 2021). Consequently, the design, operations management, organization of resources, marketing and communications and actual provision of services have a lot to benefit from adopting and disseminating smart technologies in the service organizations and across service partners, to ultimately influence wider service ecosystems (Priporas et al., 2017). In this vein, value creation as influenced by sophisticated apps and other smart technologies is an area of interest for both marketing scholars and practitioners and requires further investigation to support marketing effectiveness in the Industry 4.0 era (Ekren et al., 2023; Osadchaya et al., 2024). Notwithstanding the opportunities that have emerged from this new technological environment, various challenges also need to be addressed. These challenges span across service ecosystems and influence the roles and actions of all stakeholders involved. Thus, there are organizational challenges, ethical considerations, environmental concerns and technological challenges that may need to be tackled, mitigated or even avoided (Marder et al., 2024).
Keywords: smart technology; technological environment; service industry; tourism